Analysis of Physical Education and Sports Learning Literacy for Male Students at SMP Negeri 1 Pagu, Kediri Regency - Nur Irfan, Raihan; Harmono, Setyo; Puspodari (NUSANTARA SPORTA: Jurnal Pendidikan dan Ilmu Keolahragaan, 2024)
The aim of the research is to determine the literacy of Physical Education and Sports Learning among male students at SMP Negeri 1 Pagu, Kediri Regency. This type of research is descriptive quantitative. The sample in this research was 30 male students of SMP Negeri 1 Pagu Kediri. Data collection uses observation, interview and documentation techniques. Next, the data was analyzed using descriptive data analysis techniques. The results of the research show that indicators of student reasoning are still lacking, adequate meaning construction, good discrimination, poor critical insight and good critical thinking. The conclusion of this research shows that the literacy level of Physical Education and Sports among students at SMP Negeri 1 Pagu, Kediri Regency is still lacking